Web-Based Online Inventory Booking System: A Case Study of Ngawen Muntilan Magelang Indonesia - Nugroho Agung Prabowo; Irsatu Nurhayadin; Arif Setyo Wicaksono; Zuan Afrisaul Haq; Mukhtar Hanafi; Bambang Pujiarto; R. Arri Widyanto (IndoCompt Publisher, 2025)
This study describes the development and implementation of a web-based online borrowing and booking system for inventory items in the Dusun Ngawen community, Muntilan, Magelang. The system was designed using an Object-Oriented Programming (OOP) approach to ensure a modular, flexible, and efficient structure for future scalability. The research began with user requirement analysis involving residents and inventory managers, followed by OOP-based architectural design, code implementation using encapsulation, inheritance, and polymorphism principles, and functionality testing before online deployment. The resulting system enables residents to view available inventory, submit borrowing requests, and track borrowing status in real-time through a responsive web interface. The system also features an admin dashboard with integrated data management for user registration, item availability, and borrowing transactions. Results show that the system effectively overcomes communication barriers in traditional inventory borrowing processes, ensures transparency of item availability, and streamlines monitoring and confirmation processes. This innovation not only improves service efficiency within the RT environment but also provides a reference framework for similar community-based system developments. However, optimal utilization requires socialization and training for residents and managers. Overall, the implementation demonstrates that web-based technology with OOP design can significantly advance inventory management practices in local residential communities